La autoantigen is required for the internal ribosome entry site-mediated translation of Coxsackievirus B3 RNA - Ray, Partho Sarothi (Oxford University Press, 2002)
Translation initiation in Coxsackievirus B3 (CVB3) occurs via ribosome binding to an internal ribosome entry site (IRES) located in the 5′-untranslated region (UTR) of the viral RNA. This unique mechanism of translation initiation requires various trans-acting factors from the host. We show that human La autoantigen (La) binds to the CVB3 5′-UTR and also demonstrate the dose-dependent effect of exogenously added La protein in stimulating CVB3 IRES-mediated translation. The requirement of La for CVB3 IRES mediated translation has been further demonstrated by inhibition of translation as a result of sequestering La and its restoration by exogenous addition of recombinant La protein. The abundance of La protein in various mouse tissue extracts has been probed using anti-La antibody. Pancreatic tissue, a target organ for CVB3 infection, was found to have a large abundance of La protein which was demonstrated to interact with the CVB3 5′-UTR. Furthermore, exogenous addition of pancreas extract to in vitro translation reactions resulted in a dose dependent stimulation of CVB3 IRES-mediated translation. These observations indicate the role of La in CVB3 IRES-mediated translation, and suggest its possible involvement in the efficient translation of the viral RNA in the pancreas.